Triclosan and triclocarban weaken the olfactory capacity of goldfish by constraining odorant recognition, disrupting olfactory signal transduction, and disturbing olfactory information processing. (15th April 2023) - Huang, Lin; Zhang, Weixia; Tong, Difei; Lu, Lingzheng; Zhou, Weishang; Tian, Dandan; Liu, Guangxu; Shi, Wei
Highlights: TCS/TCC treatment caused deterioration of the olfactory ability of goldfish. TCS/TCC reduced the expression of olfactory receptors in the olfactory epithelium. TCS/TCC restricted the transformation of odorant stimulation into electric signals. TCS/TCC induced apoptosis and inflammation in the olfactory bulb. Abstract: Recently, increased production and consumption of disinfectants such as triclosan (TCS) and triclocarban (TCC) have led to massive pollution of the environment, which draws global concern over the potential risk to aquatic organisms. However, the olfactory toxicity of disinfectants in fish remains elusive to date. In the present study, the impact of TCS and TCC on the olfactory capacity of goldfish was assessed by neurophysiological and behavioral approaches. As shown by the reduced distribution shifts toward amino acid stimuli and hampered electro-olfactogram responses, our results demonstrated that TCS/TCC treatment would cause deterioration of the olfactory ability of goldfish. Our further analysis found that TCS/TCC exposure suppressed the expression of olfactory G protein-coupled receptors in the olfactory epithelium, restricted the transformation of odorant stimulation into electrical responses by disturbing the cAMP signaling pathway and ion transportation, and induced apoptosis and inflammation in the olfactory bulb. In conclusion, our results demonstrated that an environmentally realistic level of TCS/TCC would weaken the olfactory capacity of goldfish by constraining odorant recognition efficiency, disrupting olfactory signal generation and transduction, and disturbing olfactory information processing. Graphical abstract: Image, graphical abstract